DISMANTLING PUBLIC SERVICE PRACTICES IN THE ISSUANCE OF RESIDENT IDENTITY CARD IN TEGAL HARUM VILLAGE, DENPASAR - Merta, I Nengah; Anom Kumbara, A.A. Ngurah; Wirawan, A.A. Bagus; Darmana, Ketut (E-Journal of Cultural Studies; Volume 12, Number 2, May 2019, 2019)
The Bali bombing tragedy of 12 October 2002 has killed hundreds of souls. The event brought about the impact of major changes for Balinese people. Uncontrolled migrants are regarded as one of the causes of the Bali bomb tragedy. The event then took the policy to control the attendance of migrants (TAMIU) through the decree of the mayor of Denpasar No. 610, the year 2002 that is a concern that migrants living in Denpasar must have a resident identity card Entrants (KIPP). The purpose of this research is to understand and analyze the Praaktik of KIPP's publishing services as a control device of expat resident in Denpasar City based on the spirit of prod Dharma. Data collection methods are performed with observations, interviews, and documentation. Technical data is done qualitatively. The research finds that KIPP's publishing has not been successful as a control device for the number of migrants. KIPP's service practices are inefficient, not transparent and unaccountable. The reason is that the existence of dualism of customary village and the village of Dinas, human resources are still weak, facilities and infrastructure that is not refresentative that implicates to the open opportunities of corruption, collusion and nepotism, public service costs High, the number of unsynced population at the village level, sub-districts, or even provincial-level patents and increasing social pathology. This paper suggests the need for the assertiveness of the rules between the authority of indigenous villages and Dinas, need to increase the quality of human resources, especially the lower level, and the strict action to actors who are not disciplined in carrying out their duties.   Keywords: public service, excellent service, the identity of the resident, prod Dharma.